Pengembangan Model PBL (Project Based Learning) Berbasis Potensi Lokal dalam Pembelajaran Menulis Teks Drama di SMA Negeri Kabupaten Kubu Raya - Fitriani, Fitriani; Arni, Arni (LP. Ma'arif Janggan Magetan, 2023)
This research is motivated by the low ability to write drama texts of high school students in Kubu Raya Regency, West Kalimantan, which is still below the KKM. The low ability of students to write drama texts is caused by students' lack of interest and students' difficulty in determining drama themes. The learning model used by teachers is still not in line with expectations. The learning model is still not varied. Such conditions indicate gaps that need to be resolved. The Project Based Learning model based on local potential is an alternative for improving the ability to write drama texts. This research aims to describe the profile of learning to write drama texts, design a Project Based Learning model based on local potential in learning to write drama texts and develop a Project Based Learning model based on local potential in learning to write drama texts as well as the responses of participants after this model is implemented. This R&D research uses the Plomp model which consists of stages, preliminary investigation, design, realization/construction, test, evaluation and revision, implementation. Data collection techniques in this research were observation, questionnaires, interviews and tests. The data analysis used was qualitative descriptive. The test results of the implementation of the Project Based Learning model based on local potential in learning to write drama texts at SMAN Kubu Raya Regency, West Kalimantan can improve the ability to write drama texts. The final Project Based Learning model based on local potential in learning to write drama texts is a guide to the Project Based Learning model based on local potential in learning to write drama texts.